2009
DOI: 10.1002/cnm.1298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flow vortex on a chorded mitral valve in the left ventricle

Abstract: SUMMARYAn Immersed Boundary fluid-structure interaction model is developed to investigate the dynamic behaviour of a prosthetic chorded mitral valve (MV) inside the left ventricle (LV). In order to simulate more realistic physiological flow conditions, in vivo magnetic resonance images of the LV are used to determine the anatomical structure and the motion of the LV. The LV geometry and its motion are incorporated into the dynamic MV model. This model allows us to investigate the influences of the flow vortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…These findings highlight the importance of accounting for the bending stiffness in the dynamic simulation of the mitral valve. The current model has been improved from our previous mitral valve models (Watton et al 2007(Watton et al , 2008Griffith 2009;Yin et al 2010) in several important aspects. Pressure boundary conditions are imposed, and the mechanical representation has been improved by accounting for the bending rigidity of the leaflets and the chordae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings highlight the importance of accounting for the bending stiffness in the dynamic simulation of the mitral valve. The current model has been improved from our previous mitral valve models (Watton et al 2007(Watton et al , 2008Griffith 2009;Yin et al 2010) in several important aspects. Pressure boundary conditions are imposed, and the mechanical representation has been improved by accounting for the bending rigidity of the leaflets and the chordae.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above approaches, in which native human or animal valves are of primary interest, our group has developed a sequence of fully three-dimensional fluid-structure interaction models of a polyurethane prosthetic mitral valve (Watton et al 2007(Watton et al , 2008Griffith et al 2009;Yin et al 2010). In these studies, the dynamic behaviour of a three-dimensional chorded mitral prosthesis is modelled using the immersed boundary (IB) method, which accounts for the fluid-structure interaction between the blood flow and the mitral valve leaflets.…”
Section: Introductionmentioning
confidence: 98%
“…Although this approximation is reasonable when simulating the fully opened or closed configurations, studies have pointed out that the flow patterns inside the LV have important effects on MV functions. For example, it has been shown that vortex formation helps the MV closure at end鈥恉iastole …”
Section: Modelling MV With Fluid鈥恠tructure Interactionmentioning
confidence: 99%
“…Indeed, Lau et al [12] compared the MV dynamics in a straight tube and a U-shaped ventricle, and found that when the MV is mounted into a LV, the transvalvular velocity is slower compared to the one estimated using a tubular geometry. Yin et al [19] modelled a chordaed MV inside a LV and identified fluid vortices associated with the LV motion. However, their LV motion is modelled as a set of prescribed moving boundary, and the MV model is simply constructed using a network of linear elastic fibres.…”
Section: Introductionmentioning
confidence: 99%